Striking the Right Chord: Signaling Enigma during Root Gravitropism - Singh, Manjul; Gupta, Aditi; Laxmi, Ashverya (Frontiers in Plant Science, 2017)
Plants being sessile can often be judged as passive acceptors of their environment. However, plants are actually even more active in responding to the factors from their surroundings. Plants do not have eyes, ears or vestibular system like animals, still they “know” which way is up and which way is down? This is facilitated by receptor molecules within plant which perceive changes in internal and external conditions such as light, touch, obstacles; and initiate signaling pathways that enable the plant to react. Plant responses that involve a definite and specific movement are called “tropic” responses. Perhaps the best known and studied tropisms are phototropism i.e. response to light, and geotropism i.e. response to gravity. A robust root system is vital for plant growth as it can provide physical anchorage to soil as well as absorb water, nutrients and essential minerals from soil efficiently. Gravitropic responses of both primary as well as lateral root thus become critical for plant growth and development. The molecular mechanisms of root gravitropism has been delved intensively however, the mechanism behind how the potential energy of gravity stimulus converts into a biochemical signal in vascular plants is still unknown, due to which gravity sensing in plants still remains one of the most fascinating questions in molecular biology. Communications within plants occur through phytohormones and other chemical substances produced in plants which have a developmental or physiological effect on growth and development. Here, we review current knowledge of various intrinsic signaling mechanisms that modulate root gravitropism in order to point out the questions and emerging developments in plant directional growth responses. We are also discussing the roles of sugar signals and their interaction with phytohormone machinery, specifically in context of root directional responses.